A prospective study comparing patient-reported outcomes in Crohn's disease. Issue 1 (January 2020) - Hoekman, Daniël R.; Löwenberg, Mark; van den Brink, Gijs R.; Ponsioen, Cyriel Y.; Benninga, Marc A.; D'Haens, Geert R.
Abstract : Background: Patient reported outcomes are important in Crohn's disease. In this prospective cohort, we investigated the performance of the Bristol Stool Form Scale (BSFS) and a visual analog scale (VAS) for abdominal pain as outcome measures in Crohn's disease. Methods: Patients with active Crohn's disease starting glucocorticoids or anti-tumor necrosis factor were included. Before treatment and 10 weeks later we collected: clinical activity [Harvey Bradshaw Index (HBI) and Crohn's-Disease-Activity-Index (CDAI)], serum C-reactive protein (CRP) and fecal calprotectin, and BSFS (1–7) and a 100-mm VAS based on a 7-day diary. Clinical response was defined as a reduction by at least 3 and at least 100 of HBI and CDAI, respectively. Fecal calprotectin-response and CRP-response were defined as reduction of at least 50%. Results: Thirty-eight patients completed follow-up. At baseline, BSFS-parameters correlated more strongly with clinical activity (range: r s : 0.31–0.74) than with CRP ( r s : −0.01 to 0.16) and fecal calprotectin ( r s : 0.14–0.26). VAS scores correlated very weakly to moderately with clinical activity ( r s : 0.18–0.45), and weakly to moderately with CRP ( r s : 0.24–0.34) and fecal calprotectin ( r s : 0.35–0.43). Changes in VAS scores correlated moderately to strongly ( r s : 0.55–0.71) with changes in clinical activity, and weakly with changes in CRP and fecal calprotectin ( r s : 0.21–0.35). Changes in BSFS parameters correlated weakly to moderately ( r s : 0.23–0.53) with changes in clinical activity, and very weakly to weakly ( r s : 0.01–0.35) with changes in CRP and fecal calprotectin. Responsiveness of VAS and BSFS was moderate to high (Guyatt's statistic 0.41–2.17) and highly dependent on the definition of response. Conclusions: The BSFS and a VAS appear to be responsive with moderate-to-strong construct validity to monitor patients with Crohn's disease. Abstract : Supplemental Digital Content is available in the text.